Peningkatan Kompetensi Guru BK dalam Edukasi Pencegahan Pelecehan Seksual Remaja Melalui Pelatihan Pemanfaatan Canva di Kota Payakumbuh - Nurfarhanah, Nurfarhanah; Cusinia, Azahra Hardi; Febriani, Rahmi Dwi; Putriani, Lisa; Zahri, Triave Nuzila; Sukmawati, Indah; Maharani, Violanisa (Transpublika Publisher, 2025)
Digital literacy has become an essential competency for Guidance and Counseling teachers in the era of educational technology. BK teachers are expected to utilize digital media to educate students in a communicative, creative, and contextual manner. This community service program aimed to enhance the competencies of secondary school BK teachers in Payakumbuh City in using Canva as an educational medium for preventing sexual harassment among adolescents. The activity was conducted on August 9, 2025, at the Payakumbuh City Education Office by a team of lecturers and students from the Guidance and Counseling Professional Education Program, Faculty of Education, Universitas Negeri Padang (FIP UNP), as part of the Program Integrasi Prodi dan Nagari (PIPN). A total of 38 BK teachers participated in the hands-on training, which resulted in five digital posters themed on sexual harassment prevention. The activity results showed significant improvement in three aspects: technical skills in designing with Canva, internalization of moral values such as respect for personal boundaries and consent, as well as the ability to convert preventive counseling messages into visual media that is attractive and contextual for adolescents. This activity effectively strengthened the dual role of guidance and counseling teachers as skilled digital literacy agents while simultaneously protecting students through visual campaigns in schools, aligned with national policies on sexual violence prevention.